PROSEDUR PENGUJIAN SUBSTANTIF TERHADAP ASET TETAP PADA PT ABC OLEH KANTOR AKUNTAN PUBLIK HERTANTO, GRACE, KARUNAWAN - Ferin Octafiani Putri, (2021)
Auditing is the collection and evaluation of evidence for information to report and determine the level of conformity of the information with the criteria that have been set and implemented by an independent party who has competence in their field. Fixed assets by definition are assets or assets that are tangible and have a useful life of more than one year. Fixed assets are used in the operational activities of a company to create goods or services continuously and tend not to be easily converted into cash. Determining the fairness of the presentation of financial statements on the balance of fixed assets in a company is a very important thing to do. The determination can be made by substantively testing the fixed assets by the Public Accounting Firm. Substantive testing is an important procedure in an audit process in a company. The purpose of doing substantive testing is to ensure the existence, completeness, and occurrence of things related to the company's fixed assets in accordance with those on the balance sheet. In this case, the external auditor is allowed to assess and provide an opinion on the fairness of the presentation of a company's financial statements. The conclusion that can be drawn is that substantive testing of the balance of PT ABC's fixed assets by KAP HGK is to determine materiality, request a detailed list of fixed assets, recalculate fixed assets depreciation, draw samples to examine physical fixed assets, physical inspection of fixed assets, and make minutes.